English Learning Strategy and Learner’s Cultural Background - Ningtyas, Tutik Ratna; Amirudin, Amirudin (Ainara Journal (Jurnal Penelitian dan PKM Bidang Ilmu Pendidikan), 2023)
English as a second or foreign language, it is often found that learning English is not an easy task, In order to overcome that difficulty, there are many factors that can be counted in, including learning strategies. Learning strategies are considered as self-improvement devices that might be driven by learners themselves or by teachers. In addition, culture might play important role in determining learning strategy since culture cannot be separated from language as well as its learning/teaching. This paper attempts to provide a learning strategy that might meet with Indonesian students’ cultural background. As noticed, Indonesians commonly hold mutual assistance as one of life principles. Hence, this paper also provides an explanation concerning learning strategy which may meet with mutual assistance principle: collaborative learning.